The Role of Dynamic Capability and Product Innovation to Increase Competitive Advantage - Anak Agung Dwi Widyani; I Nengah Suardhika (Universitas Warmadewa, 2024)
This study aims to determine dynamic capability and product innovation in determining competitive advantage in SMEs woven fabric industries (endek) in the Klungkung Regency, Bali Province. The research approach used is descriptive analysis with a quantitative approach using the Smart PLS programme. The population in this study is the owner of a woven fabric business (endek) in the Klungkung Regency, Bali Province. The results showed that dynamic capability could directly determine the product innovation and competitive advantage of woven fabric SMEs (endek) in the Klungkung Regency, Bali Province. However, product innovation can produce a competitive advantage for woven fabric SMEs (endek) in the Klungkung Regency, Bali Province. The research results also show that product innovation is a mediator in the influence of dynamic capability on competitive advantage.